ANALISIS KESALAHAN SISWA KELAS VIII DALAM MENYELESAIKAN SOAL MATEMATIKA DITINJAU DARI TINGKAT KEMAMPUAN MATEMATIS - Putri, Aulia Adytia; Priatna, Nanang; Kusnandi, Kusnandi (Universitas Bhinneka PGRI, 2023)
This study purpose is to describe the errors of grade VIII students when solving SPLDV problems based on error analysis according to Newman procedure in terms of students' mathematical ability level. This research method is qualitative descriptive research. 9 students from SMPN 15 Bandung with different math abilities were selected, namely 3 students at each level of high, medium and low math ability as study subjects. Data analysis techniques are performed in 3 steps, namely data reduction, data presentation and conclusion. The data validity technique uses the triangulation method to compare the results of the written test with the results of the interviews. The results show that students with high math ability tend to make mistakes at the transformation stage, students with average math ability tend to make mistakes at the transformation stages and coding, while students with low math abilities tend to make mistakes. . at most types of errors, from understanding, transformation, processing and coding stages.